Lithium‐Ion Batteries: Operando Magnetometry Probing the Charge Storage Mechanism of CoO Lithium‐Ion Batteries (Adv. Mater. 12/2021). Issue 12 (23rd March 2021) - Li, Hongsen; Hu, Zhengqiang; Xia, Qingtao; Zhang, Hao; Li, Zhaohui; Wang, Huaizhi; Li, Xiangkun; Zuo, Fengkai; Zhang, Fengling; Wang, Xiaoxiong; Ye, Wanneng; Li, Qinghao; et al.
Abstract : In article number 2006629, Hongsen Li, Yunze Long, Qiang Li, and co‐workers use an advanced operando magnetometry technique to probe the charge‐storage mechanism of CoO lithium‐ion batteries, showing that the anomalous discharge capacity in this particular system is associated with both the reversible formation of a spin capacitor and the growth of a polymeric film at low voltages. The key catalytic role of metallic Co in assisting the polymeric film formation is demonstrated, which is helpful for the design of new types of energy‐storage devices and improving the energy density for future battery designs.